Eukaryotic gene regulation: from chromatin to transcription to mRNA processing - Carey, Michael; Smale, Stephen (Henry Stewart Talks, 2007)
Introduction to the series by Professor Michael Carey and Professor Stephen Smale
Archived at 2016/04/17